Feminist Storytelling and Narratives of Intersectionality. - Ilmonen, Kaisa (Signs: Journal of Women in Culture & Society)
Storytelling is a focal part of any critical work. This article maps what kinds of narratives have been included in the often heated discussions about intersectionality during the past ten years. Scholarly discussions, including intersectionality, also create their own plot patterns, which then regulate what can be argued or should not be argued, what blind spots need to be illuminated, or which weaknesses must be revised. What can we know about intersectionality in the light of scholarly storytelling? How have narrative habits of feminist storytelling affected the development of intersectionality? As a fast-traveling theory, intersectionality has been examined and defined closely in academic discussions, rendering it a target of heated debates. Here, I would like to concentrate on enthusiasm about intersectionality and ask: do we risk losing ethical enthusiasm and compassion in suspicious, fault-finding feminist storytelling? I will first consider feminist storytelling along the lines provided by Rita Felski in The Limits of Critique , Robyn Wiegman in Object Lessons , and Clare Hemmings in Why Stories Matter. After that, I will analyze some recurrent story lines that emerge in debates about intersectionality, story lines concerning genealogy and originalism, intersectionality's relation to black feminism, narratives of revision and correction, and numerous others. In conclusion, I offer an alliance with Felski's postcritical reading to develop new enthusiasm about, and engagement with, intersectionality.